Marital Age Gaps and Educational Homogamy - Evidence from a Compulsory Schooling Reform in the UK - Timo Hener; Tanya Wilson (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
We investigate the impact of a compulsory schooling reform on marriage market matching using a regression discontinuity design. Our results imply that the formally gender-neutral educational reform has asymmetric impacts for men and women, owing to the pervasive marital age gap and the birthdate discontinuity. We show that treated women decrease the marital age gap to avoid marrying less qualified men. Treated men in contrast are able to marry similarly educated women without substantially changing the age gap. Our estimates indicate that the disruptions for cohorts around the introduction of the reform are economically significant.
Keywords: I28; J12; 330; Marital sorting; spousal age gap; compulsory schooling.